2007
DOI: 10.1111/j.1939-1676.2007.tb01945.x
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Web‐Based Health Survey of Retired Racing Greyhounds

Abstract: Background: Adoption of retired racing Greyhounds has become increasingly popular during the past decade. To date, research has focused on the physiologic and clinicopathologic peculiarities of Greyhounds but there is little published information on disease prevalence in the breed.Objective: The objective of this study is to determine the prevalence of disease in retired racing Greyhounds. Animals: In this study, 747 Greyhounds were used. Methods: A standardized survey method was used, and survey responses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 22 publications
1
50
1
Order By: Relevance
“…Previous studies showed a high incidence of PHMs in adult boxers (Höglund et al 2004, Koplitz et al 2006, Bussadori et al 2009): this study included one adult boxer that was not diagnosed with PHM. Additionally, athletic dogs predisposed to PHMs were not enrolled (Stepien et al 1998, Fabrizio et al 2006, Lord et al 2007, Bavegems et al 2011. Conversely, some breeds of dogs were over-represented in this study, such as Yorkshire terriers, German shepherd dogs, French bulldogs, Labrador retrievers and golden retrievers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed a high incidence of PHMs in adult boxers (Höglund et al 2004, Koplitz et al 2006, Bussadori et al 2009): this study included one adult boxer that was not diagnosed with PHM. Additionally, athletic dogs predisposed to PHMs were not enrolled (Stepien et al 1998, Fabrizio et al 2006, Lord et al 2007, Bavegems et al 2011. Conversely, some breeds of dogs were over-represented in this study, such as Yorkshire terriers, German shepherd dogs, French bulldogs, Labrador retrievers and golden retrievers.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological heart murmurs may occur because of alterations in other organ systems such as anaemia, fever or systemic arterial hypertension (also referred to as 'functional' murmurs in this context); and in dogs under the age of 6 months (also referred to as 'innocent' murmurs) (Bonagura 2002). Although murmurs in mature dogs are frequently indicative of pathological conditions (Bélanger and Côté 2010), PHMs during adulthood have been described in some breeds, such as boxers (Höglund et al 2004, Koplitz et al 2006, Bussadori et al 2009) and athletic dogs (Stepien et al 1998, Fabrizio et al 2006, Lord et al 2007, Bavegems et al 2011. Physiological heart murmurs have also been described occasionally in adult dogs of other breeds; it has been assumed that these PHMs may be attributable to an increased sympathetic tone, possibly secondary to anxiety (Pedersen et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly IGF1 and its associated regions are a major contributing locus in size diversity in dogs, accounting for about 50% of the genetic variation in size [95]. Osteosarcoma is particularly prevalent in retired racing Greyhounds, possibly implicating stress or trauma in the aetiology of the disease in this breed [83, 96]. A familial incidence has been observed in Saint Bernards [91] and more recently a study modelling the transmission of osteosarcoma in a population of over 1000 Scottish deerhounds estimated heritability at 0.69 and modelling suggested that a major gene with dominant effect would explain the pattern of transmission [42].…”
Section: Osteosarcomamentioning
confidence: 99%
“…Both human and canine OS most commonly arise at the ends of the long bones of the limbs and metastasize readily, usually to the lungs [9]. Unlike human OS, canine OS is a highly heritable disease with some large and giant dog breeds at >10× increased risk, notably greyhounds (mortality from OS = 26%), Rottweilers (17%), and Irish wolfhounds (IWH, 21%) [10-12]. While size and hormonal factors influence risk, variable rates among the larger size breeds suggest breed-specific risk factors [13].…”
Section: Introductionmentioning
confidence: 99%